Efficacy of tocilizumab in resistant forms of Thyroid Eye Disease - Marković Bojan; Joksimović Nata; Janić Tamara; Babić Jovana; Miletić Marija; Stojković Mirjana; Nedeljković-Beleslin Biljana; Ćirić Jasmina; Žarković Miloš (Medicinski Glasnik Specijalne Bolnice za Bolesti Štitaste Žlezde i Bolesti Metabolizma "Zlatibor")
Thyroid Eye Disease (TED), formerly known as Graves' orbitopathy, is an autoimmune disorder affecting orbital tissues. The Clinical Activity Score (CAS) is used to evaluate TED activity. A score ≥3 indicates active disease, warranting immunomodulatory therapy. Intravenous corticosteroids (IVCS) are the first-line treatment. However, studies show 20-30% of patients with moderately severe active TED have an inadequate response to corticosteroids. For patients with poor response or tolerance to steroids, tocilizumab offers an effective alternative. We present a case of a 49-year-old female with moderately severe, active, corticosteroid-resistant TED. After failure of two corticosteroid regimens (4.5 g and 5 g), biological therapy with tocilizumab (6 cycles of 600 mg every 4 weeks) was initiated. Clinical response was monitored using NOSPECS, CAS, and the Gorman-Bahneman diplopia classification. This case confirms the potential efficacy of tocilizumab in managing corticosteroid-resistant, moderately severe active TED.